2020
DOI: 10.7717/peerj.9429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors associated with latent tuberculosis infection in a Latin American region

Abstract: Tuberculosis (TB) represents a health problem in Colombia, and its control is focused on the search for contacts and treatment of TB cases underscoring the role of latent tuberculosis infection (LTBI) as a reservoir of Mycobacterium tuberculosis. The burden of LTBI in Colombia is unknown. We aimed to estimate the prevalence of LTBI and identify the associated risk factors. In this cross-sectional study, we recruited participants from four health care centers in Cali, Colombia. The participants were eligible if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
5
0
4
Order By: Relevance
“…Dampak terhadap kesehatan khususnya penularan berbagai penyakit infeksi khususnya tuberkulosis tidak bisa dihindari berhubungan dengan interaksi sosial diantara masyarakat. Sebagai penyakit yang ditularkan melalui interaksi sosial, penderita tuberkulosis baik fase aktif maupun fase laten [20] serta a penderita multi drug resistance (MDR) menjadi semakin sulit diobati jika tidak dikendalikan dan dipantau secara intensif [21].…”
Section: Pendahuluanunclassified
“…Dampak terhadap kesehatan khususnya penularan berbagai penyakit infeksi khususnya tuberkulosis tidak bisa dihindari berhubungan dengan interaksi sosial diantara masyarakat. Sebagai penyakit yang ditularkan melalui interaksi sosial, penderita tuberkulosis baik fase aktif maupun fase laten [20] serta a penderita multi drug resistance (MDR) menjadi semakin sulit diobati jika tidak dikendalikan dan dipantau secara intensif [21].…”
Section: Pendahuluanunclassified
“…[ 10 ] Study concluded that prevalence of infection is higher among males (25.7%) when compared to female sex (20.7%) similar to a study conducted using TST. [ 15 ] Failure to establish a significant difference could be due to inadequate power of the present study to establish the causation between these factors and infection, which was not the primary objective of the present study. Due to the same reason present study couldn’t establish a statistical significance on either socioeconomic status of participant or tobacco smoking status, though these factors are widely quoted as risk factors for infection.…”
Section: Discussionmentioning
confidence: 87%
“…Others include the low quality of health services, such as accessibility, health facilities, lack of training, health workers, and information systems ( 13 ). TB occurs mainly in adults ( 3 , 16 , 34 ) with an increasing trend in children ( 20 ), and in the elderly ( 20 , 22 ). Household contact is the main source of transmission to children ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of tuberculosis among Taiwanese migrants is higher than in the local population ( 16 ). The Chinese migrant population had a higher risk of TB incidence compared with the local population ( 31 ).…”
Section: Resultsmentioning
confidence: 99%